2017
DOI: 10.1371/journal.pone.0181476
|View full text |Cite
|
Sign up to set email alerts
|

Cx47 fine-tunes the handling of serum lipids but is dispensable for lymphatic vascular function

Abstract: Mutations in the gap junction protein connexin47 (Cx47) are associated with lymphedema. However, the role of Cx47 in lymphatic pathophysiology is unknown. We demonstrate that Cx47 is expressed in lymphatic endothelial cells by whole-mount immunostaining and qPCR. To determine if Cx47 plays a role in lymphatic vessel function we analysed Cx47-/- mice. Cx47-deficiency did not affect lymphatic contractility (contractile amplitude or frequency) or lymphatic morphology (vessel diameter or number of valves). Interst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 63 publications
1
27
2
Order By: Relevance
“…Although we found no evidence for a direct involvement of Cx47 in the peripheral cellular immune response, Cx47 expression in lymphatic epithelium (Meens et al, 2017;Munger, Davis, & Simon, 2017) may suggest a possible role in peripheral immune reactions.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Although we found no evidence for a direct involvement of Cx47 in the peripheral cellular immune response, Cx47 expression in lymphatic epithelium (Meens et al, 2017;Munger, Davis, & Simon, 2017) may suggest a possible role in peripheral immune reactions.…”
Section: Discussioncontrasting
confidence: 90%
“…Although we found no evidence for a direct involvement of Cx47 in the peripheral cellular immune response, Cx47 expression in lymphatic epithelium (Meens et al, ; Munger, Davis, & Simon, ) may suggest a possible role in peripheral immune reactions. This could be relevant for the heightened CNS B cell response in Cx47KO EAE brains, since the pathway from brain lymphatics to draining cervical lymph nodes may modulate the CNS immune response (Louveau, Da Mesquita, & Kipnis, ).…”
Section: Discussioncontrasting
confidence: 77%
“…Although mutations in the GJC2 gene predispose for human lymphedema, Cx47 expression is only sporadically detected in lymphatic ECs of the embryonic and adult mouse (22,62). Moreover, Cx47 deficiency did not affect lymphatic contractility or morphology nor interstitial fluid drainage in adult mice (62). It has recently been reported that human venous valve disease may be caused by mutations in the GJC2 gene.…”
Section: Connexins In Lymphatic Edemamentioning
confidence: 99%
“…Mice with a lymphatic EC-specific ablation of Cx43 show a delayed initiation, reduced frequency and incomplete maturation of lymphatic valves and altered lymphatic capillary patterning, resulting in leaky valves, insufficient lymphatic transport and a high incidence of lethal chylothorax, a milky effusion around the heart and lungs, in the first 6 months of life (61). Although mutations in the GJC2 gene predispose for human lymphedema, Cx47 expression is only sporadically detected in lymphatic ECs of the embryonic and adult mouse (22,62). Moreover, Cx47 deficiency did not affect lymphatic contractility or morphology nor interstitial fluid drainage in adult mice (62).…”
Section: Connexins In Lymphatic Edemamentioning
confidence: 99%
“…Whether a direct involvement of Cx47 in the peripheral cellular immune response could contribute to the exacerbated EAE pathology in the CNS of Cx47 KO mouse remains to be clarified. Cx47 expression in the lymphatic epithelium [106,107] suggests a possible role in peripheral immune reactions. This could be one of the reasons for the heightened B-cell response in Cx47 KO EAE brains, since the pathway from brain lymphatics to draining Figure 1.…”
Section: Oligodendrocyte Connexin Pathology In Experimental Autoimmunmentioning
confidence: 99%